21 Five years of EMA-approved systemic cancer therapies for solid tumours – a comparison of two thresholds for meaningful clinical benefit. (20th August 2018) - Grössmann, Nicole; Paggio, Joseph Del; Wolf, Sarah; Sullivan, Richard; Booth, Christopher M; Rosian, Katharina; Emprechtinger, Robert; Wild, Claudia
Abstract : Objectives: Approximately, 800 drugs and vaccines are currently under investigation in clinical trials for the treatment of cancer. Roughly, 80% of those are first-in-class therapies, and around 73% are intended as personalised and, therefore, targeted medicines. Therefore, several societies have proposed frameworks that attempt to support the optimal use of limited health care resources, while offering a standardised and transparent tool to evaluate the benefit of novel cancer therapies. One prominent tool is the European Society for Medical Oncology Magnitude of Clinical Benefit Scale (ESMO-MCBS). Our objectives were to investigate the extent of European Medicines Agency (EMA)-approved cancer drugs that meet the threshold for 'meaningful clinical benefit' (MCB), defined by the framework, and determine the change in the distribution of grades when an adapted version that addresses the scale's limitations is applied. Method: We identified all approval studies of cancer drugs indicated for solid tumours that received marketing authorisation by the EMA between 1 st January 2011 and 31 st December 2016. We previously proposed adaptations to the ESMO-MCBS addressing its main limitations, including the use of the lower limit of the 95% confidence interval in assessing the hazard ratio. To assess the MCB, both the original and adapted ESMO-MCBS were applied to the respective approval studies. Results: In total, we identified 70 approval studies for 38 solid cancer drugs. 21% of therapies met the MCB threshold by the original ESMO-MCBS criteria. In contrast, only 11% of therapies met the threshold for MCB when the adapted ESMO-MCBS was applied. Thus 89% and 79% of therapies did not meet the MCB threshold in the adapted and original ESMO-MCBS, respectively. Conclusions: In most of the cancer drugs, the MCB threshold is not met at the time of approval when measured using both ESMO-MCBS scales. Since approval status does not translate into a MCB, stakeholders and decision makers need to continually assess the benefitrisk ratio of new cancer drugs to ensure a balanced and an equitable distribution of resources in our health care systems.